Soil Carbon, Nitrogen, pH, and Crop Yields in Winter Wheat–Spring Pea Systems. (1st July 2018) - Awale, Rakesh; Machado, Stephen; Rhinhart, Karl
Abstract : Core Ideas: Under wheat–pea, reduced tillage increased SOC, TN, and pea yields over fall plowing. No‐till decreased surface soil pH and wheat yields relative to fall plowing. Spring plowing minimized surface soil acidification, increased crop yield, and maintained SOC and TN. Data from an ongoing winter wheat ( Triticum aestivum L.)–spring pea ( Pisum sativum L.) long‐term experiment on a Walla‐Walla silt loam (coarse‐silty, mixed, mesic Typic Haploxeroll) in eastern Oregon was used to evaluate the effects of four tillage systems [fall plow (FP), spring plow (SP), disk tillage and chisel plow (DT/CP), and no‐till (NT)] on soil pH, bulk density, soil organic carbon (SOC), total nitrogen (TN), and grain yields. Among tillage types, FP produced the lowest pea yields in 4 out of 6 crop‐years, whereas NT produced the lowest wheat yields during dry and hot crop‐years. Both NT and DT/CP had lower soil pH than FP and SP in the surface 10 cm. Soil organic C and TN were higher under NT and DT/CP than under FP and SP in the surface 10 cm. However, SP increased SOC and TN over NT at soil depth of 10 to 20 cm. Under wheat–pea, NT and DT/CP will increase SOC, TN, and pea yields but may reduce surface soil pH and decrease wheat yields relative to conventional FP. Spring plow has the potential to minimize surface soil acidification, increase crop yield, and maintain SOC and TN in wheat‐pea systems.